1999
DOI: 10.1116/1.581937
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of slider surfaces after wear using photoemission electron microscopy

Abstract: The tribo-chemical interactions between the slider and the hard disk surface strongly influence the performance properties of a disk drive. To study these interactions, uncoated and carbon coated sliders were subjected to various wear tests using different disks. After the wear, the test slider surfaces were studied by photoemission electron microscopy (PEEM) using tunable x rays produced by a synchrotron. Using PEEM, one can identify the elemental and chemical state of the surfaces with a high spatial resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…For carbon K-edge NEXAFS spectroscopy, in particular, the resolvable energy difference between the resonant X-ray excitations of a core-level (1s) electron to unoccupied molecular orbitals (either π* or σ*) allows the identification of the bonding configuration and hybridization state of carbon atoms in the near-surface region for many materials, including diamond 6,13,21,22,24,25,[33][34][35][36][37][38] , diamond-like carbon [39][40][41][42][43][44][45][46] , graphene 26,47,48 , and polymers [27][28][29][30][31][32] , as well as the determination of the surface molecular orientation of nanomaterials 18,19,49,50 and adsorbates [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…For carbon K-edge NEXAFS spectroscopy, in particular, the resolvable energy difference between the resonant X-ray excitations of a core-level (1s) electron to unoccupied molecular orbitals (either π* or σ*) allows the identification of the bonding configuration and hybridization state of carbon atoms in the near-surface region for many materials, including diamond 6,13,21,22,24,25,[33][34][35][36][37][38] , diamond-like carbon [39][40][41][42][43][44][45][46] , graphene 26,47,48 , and polymers [27][28][29][30][31][32] , as well as the determination of the surface molecular orientation of nanomaterials 18,19,49,50 and adsorbates [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Hardness becomes less of an issue since such extremely thin films cannot withstand great mechanical forces: such films serve mainly as a corrosion protection coating. Corrosion can occur as part of the tribological use of the coating, and therefore specific investigations have been made characterizing the abrasion and corrosion behavior in controlled tribological environments [74,75,76].…”
Section: Tetrahedral Amorphous Carbon (Ta-c)mentioning
confidence: 99%
“…In another study [3], worn amorphous carbon surfaces showed that certain tribochemical reactions took place when lubricants were present. The appearance of extra structures in the NEXAFS spectra were interpreted as the formation of ketone bonds (C=O) and carboxylic bonds (O=C-OH), mainly related to the chemical degradation of the lubricants during the wear process.…”
mentioning
confidence: 97%
“…NEXAFS obtained in the total electron yield (TEY) mode probes only a few nanometers deep below the surface [3] and is therefore an excellent tool to study chemical modification close to the surface as is expected to occur in the type of wear processes presented in this work.…”
mentioning
confidence: 99%
See 1 more Smart Citation